The importance of soccer-specific motor coordination in elite soccer academy players` agility testing - Zinno, R.; Di Paolo, S.; Gavioli, S.; Luca Milandri, L.; Barone, G.; Pinelli, E.; Bragonzoni, L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The assessment of agility performance is a priority for soccer academy coaches since it fosters training optimization and talent identification. The majority of agility tests used in soccer players evaluation accounts for the physical aspect of agility only. Despite their wide use, these tests do not assess soccer-specific performances. Recently, the introduction of soccer-specific motor coordinative (SSMC) elements e.g., the capacity to manage a ball while sprinting, has been claimed to improve tests sensitivity for performance and maturation. The aim of the present study was to compare the outcomes of a generic agility test with a modified version including soccer-specific skills in a cohort of young elite soccer players.